Am I A Cheater?: Pengaruh Priming dengan Subtle Linguistic in Ethical Reminder dalam mengurangi Perilaku tidak Etis Berdasarkan Jenis Kelamin - Khairina, Nadia; Raissa Dwifandra Putri; Yaumul Rahmi (Universitas Negeri Malang, 2022)
Previous studies of unethical behavior have shown that many people will engage when they have the opportunity. Several studies have shown contradictions with each other regarding fraudulent behavior between men and women. This study wanted to test whether the use of priming with subtle words could suppress the emergence of fraudulent behavior, especially when associated with gender. The study used a 2x2 experimental design ((PrimingxNonPriming)x(MalexFemale)) with 60 participants. The study used instruments in the form of mathematical problems that must be answered correctly for 60 seconds and participants can